2008
DOI: 10.1103/physrevb.77.201405
|View full text |Cite
|
Sign up to set email alerts
|

Large oscillating nonlocal voltage in multiterminal single-wall carbon nanotube devices

Abstract: We report on the observation of a non-local voltage in a ballistic (quasi) one-dimensional conductor, realized by a single-wall carbon nanotube with four contacts. The contacts divide the tube into three quantum dots which we control by the back-gate voltage Vg. We measure a large oscillating non-local voltage V nl as a function of Vg. Though a classical resistor model can account for a non-local voltage including change of sign, it fails to describe the magnitude properly. The large amplitude of V nl is due t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Spin-dependent current injected from ferro-magnetic lead demonstrates that spin scattering length is longer, at least, than the nanotube length which is typically sub-micron. [8][9][10][11][12][13][14][15][16][17][18] Moreover, spin states in carbon nanotube quantum dot seems to be independent from the orbital as shown the four-electron shell structure. [19][20][21][22][23][24][25][26][27][28] These experiments seem to be consistent with an expectation of few spin scattering events in carbon materials, because of relatively small spin-orbit interaction in a carbon atom.…”
Section: Introductionmentioning
confidence: 95%
“…Spin-dependent current injected from ferro-magnetic lead demonstrates that spin scattering length is longer, at least, than the nanotube length which is typically sub-micron. [8][9][10][11][12][13][14][15][16][17][18] Moreover, spin states in carbon nanotube quantum dot seems to be independent from the orbital as shown the four-electron shell structure. [19][20][21][22][23][24][25][26][27][28] These experiments seem to be consistent with an expectation of few spin scattering events in carbon materials, because of relatively small spin-orbit interaction in a carbon atom.…”
Section: Introductionmentioning
confidence: 95%
“…A similar four-probe study of carbon nanotubes with narrow metal contacts was reported in a recent preprint. 15 …”
mentioning
confidence: 99%
“…Another approach for these fluctuations is given by Makarovski et al [127] and Gunnarsson et al [128]. The authors found significant voltages in four-point measurements of SWCNTs in non-local geometry and traced it back to different coupling of the probes to the two orbital modes of the tube.…”
Section: Measurements In Non-local Geometrymentioning
confidence: 99%
“…First, the straight way passing the second contact in the outermost shell directly below the electrode. Although Ke et al [126] calculated that the transmission straight through the contact is drastically decreasing even for narrow contacts, Makarovski et al [127] and Gunnarsson et al [128] both found a non-constant non-local potential in SWCNTs indicating a non-vanishing transmission through the contact. For the MWCNT used in our experiment, an additional pathway that does not cross the contact is possible.…”
Section: Measurements In Non-local Geometrymentioning
confidence: 99%